Fostering Sustainability @UniTs - Paolo Bevilacqua; Barbara Campisi; Patrizia De Luca; Gianluigi Gallenti; Ilaria Garofolo (Journal of Sustainability Perspectives, 2021)
Promoting sustainability through innovative culture and models is nowadays a top task for universities. Their commitment oriented by the 17 United Nations’ Sustainable Development Goals (UN SDGs) conveys the message that sustainability is not a "luxury" but an essential vehicle through which to pursue and guarantee everyone's rights, inclusion and future.Solving complex problems calls for collaboration among communities; aware of that, Italian universities set up the RUS - Italian University Network for Sustainable Development - which acts as a model to encourage collaboration between universities and cities, to spread social innovation at local level and to provide cultural awareness at national level. The University of Trieste (UniTs) joined the network in 2017. Consistent with its strategy for sustainability, UniTs has implemented measures on the macro-context (to raise public awareness and to support research) as well as on micro-context (to orientate behaviors and habits of its community). In particular, it focused on virtuous projects such as waste management, based both on the constant reduction of waste production and on the optimization of the use of materials and products (i.e. paper, glass, reagents), along with the setting of separate waste collection to reduce disposal and favor recycling. The paper will refer on the present framework and the implementation of new integrated projects, aimed at consolidating a community attentive and aware of sustainability.